Development of Environmentally Friendly Schools to Optimize the Business of Farmer in Processing Livestock Waste - Adriani Adriani; Mairizal Mairizal; Elyanti Elyanti; Yurleni Yurleni; M Yuda Ramdani; Lasno Lasno; Suhandra Suhandra (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
This environmentally friendly school development activity is a collaboration between PUI PT Sifas (Sustainable Integrated Farming System) Universitas Jambi, with PetroChina International Jabung Ltd, and related East Tanjung Jabung Regency agencies. This activity aims to optimize the processing of livestock waste to support environmentally friendly agriculture with a zero-waste concept.  However, the obstacles faced in waste processing are that the biogas installation needs to be fixed, there are no results of compost and biourine nutrient analysis yet, the compost does not have a registered trademark. It is hoped that the group will become a training and demonstration center for environmentally friendly agriculture. This community service activities used the PAR (Participatory Action Research) approach, namely service activities that involve active community participation, starting with coordination, training, creating environmentally friendly schools, product improvement and implementation. This activity included counselling, training and building environmentally friendly schools. All activities included optimizing compost, biogas and biourine processing equipment, carrying out nutrient analysis of compost and biourine, and applying compost and biourine to plants. The extension was attended by 40 participants consisting of 35 members of farmer groups, 5 extension workers and representatives from the Department of Agriculture. Activities to improve biourine installations, compost processing, application of compost and biourine to plants. Applying compost and biourin can increase kale production by 26%, ginger by 16%, long beans by 12%, and eggplant by 14%. Local resources and adequate human resources support the development of an environmentally friendly school in Kota Baru village. Conclusion: SRL activities can have a social impact by growing participants' interest in applying compost and biourine to agricultural businesses, increasing production, reducing environmental impacts.